PENERAPAN KONSELING KELOMPOK TEKNIK SEFT UNTUK MEREDUKSI STRES AKADEMIK SISWA - Salsabila Putri Lubis; Nurussakinah Daulay (JURNAL TARBIYAH, 2024)
The aim of this research was to find out whether class XII students at PAB 8 Saentis Private High School experienced less academic stress when group counseling was applied using the SEFT technique. This research uses a quantitative methodology that will test the numerical results of the instrument. In a pre-experimental research design like this, researchers will compare students' academic stress levels before and after receiving treatment in order to provide an application of the SEFT counseling approach. One group pretest-posttest was used as the research design. Twenty students of PAB 8 Saentis Private High School participated in this research as respondents. Based on the research, it is known that class Findings from pre- and post-tests bear this out; they show that there are only small variations, not many large variations, that can help students cope with the stress they face in their learning.